Using normalization process theory to evaluate the use of patient-centred outcome measures in specialist palliative home care—a qualitative interview study - Eva Lehmann-Emele; Maximiliane Jansky; Sabina Clapham; Susanne de Wolf-Linder; Claudia Bausewein; Farina Hodiamont (BMC Palliative Care, 2024)
Abstract Background Standardised use of patient-centred outcome measures (PCOMs) improves aspects of quality of care. Normalization Process Theory (NPT) considers the social (inter-)actions of implementation processes operationalised through four constructs: coherence-building, cognitive participation, collective action and reflexive monitoring. The aim of the study was to identify barriers and enablers for the successful use of PCOMs in specialist palliative home care (SPHC) using NPT, to collect clinically meaningful and reliable data to improve patient outcomes. Methods Qualitative study using semi-structured interviews with palliative care professionals from German SPHC teams who participated in a study using PCOMs. Data were analysed using Framework analysis, and contextualised within NPT. Results Seventeen interviews across five teams were conducted. Some teams already had an understanding of what PCOMs are and how to use them, based on previous experience. In other teams, this understanding developed through the perception of the benefits (coherence). Participation and engagement depended on individuals and was decisive for coherence-building. The attitude of the management level also played a major role (cognitive participation). Integration of PCOMs into everyday clinical practice varied and depended on the manifestation of the first two constructs and other already established routines (collective action). In the context of appraisal, both positive (e.g. focus on patient) and negative aspects (e.g. additional work) of using PCOMs were mentioned (reflexive monitoring). Conclusions Although benefits of using PCOMs were partly recognised, not all teams continued standardised use. Here, not only the social (inter-)actions, but also the influence of the context (working environment) were decisive. Future implementation strategies should consider integrating PCOMs in existing electronic patient records, education sessions supporting coherence-building, internal facilitators/local champions, and ensuring frequent data analyses as it is beneficial and increases the readiness of using PCOMs.